2019
DOI: 10.1002/mrc.4812
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the electrostatic and covalent interaction between whey proteins and low methoxyl pectin using PFG‐NMR diffusometry

Abstract: As interaction between proteins and polysaccharides is expected to change the average diffusion coefficient and the distribution width, it is believed that NMR diffusometry can be a useful tool to study and quantify the interaction between whey protein isolate (WPI) and low methoxyl pectin (LMP). For this purpose, the influence of pH, dry‐heat‐treatment duration, and WPI to LMP ratio on WPI and LMP interaction was evaluated using pulsed field gradient NMR. At pH 5.0 and 5.5, approximately 40–50% of the WPI pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Previously, the formation of WPI-LMP conjugates was found to be rapid during the first two days of dry heat treatment and continuously increased at a slower rate upon extending the dry heat treatment to 16 days at 60 o C (Setiowati et al, 2018;Setiowati et al, 2016). In a recent study, 3 days of dry heat treatment was found to be the optimum duration for conjugation of α-lactalbumin and βlactoglobulin with polysaccharides (Mulcahy et al, 2016).…”
Section: Combination Of Time Temperature and Relative Humidity (Rh) O...mentioning
confidence: 98%
See 4 more Smart Citations
“…Previously, the formation of WPI-LMP conjugates was found to be rapid during the first two days of dry heat treatment and continuously increased at a slower rate upon extending the dry heat treatment to 16 days at 60 o C (Setiowati et al, 2018;Setiowati et al, 2016). In a recent study, 3 days of dry heat treatment was found to be the optimum duration for conjugation of α-lactalbumin and βlactoglobulin with polysaccharides (Mulcahy et al, 2016).…”
Section: Combination Of Time Temperature and Relative Humidity (Rh) O...mentioning
confidence: 98%
“…Similarly, emulsions stabilized by WPI-pectin conjugates were reported to be able to withstand heating at 80 and 120 o C in the presence and absence of 30-50 mM NaCl (Mulcahy et al, 2016;Setiowati et al, 2017). Furthermore, despite of the fact that WPI-pectin conjugates which were dry heat treated for only 1 day had a lower yield than those dry heat treated for 16 days, the heat stability of these two conjugates was comparable (Setiowati et al, 2017;Setiowati et al, 2018). Thus, the heat stabilizing activity of the conjugates is not influenced by the yield or degree of interaction to a large extent.…”
Section: Heat Stability Of Whey Protein-polysaccharides Conjugatesmentioning
confidence: 99%
See 3 more Smart Citations